STUDI EKSPERIMEN: PENGARUH STRATEGI PEMBELAJARAN DAN MINAT BELAJAR SISWA TERHADAP HASIL BELAJAR FIQIH - Lisa'diyah Ma'rifataini (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2012)
AbstractThis study aims at examining the effect of Cooperative learning strategies and competitive learning strategies to improve student learning outcomes in Fiqh subject associated with student interest. The research method used is experimental method with a 2x2 factorial design, the population target of which is the entire students of State Islamic Junior High Schools (MTsN) in East Jakarta. The findings of this study are: first, as a whole, the Fiqh learning outcomes of students treated using the Cooperative learning were higher than those treated using the competitive learning. Second, for students who have a high interest in learning, the Fiqh learning outcomes of students treated using the Cooperative learning were higher than those treated using the competitive learning. Third, for students who have low interest in learning, the Fiqh learning outcomes of students treated using the competitive learning were higher than those treated using the Cooperative learning. Fourth, There was an interaction effect between the Cooperative learning and the competitive learning and students’ interest in learning (high and low) to the Fiqh learning outcomes of students.AbstraksiStudi ini bertujuan untuk menguji pengaruh strategi pembelajaran kooperatif dan strategi pembelajaran kompetitif dalam meningkatkan hasil belajar siswa pada mata pelajaran Fiqh dikaitkan dengan minat belajar siswa. Metode penelitian yang dipakai adalah Eksperimen dengan desain faktorial 2x2, populasi targetnya adalah seluruh siswa MTs Negeri se-Jakarta Timur. Temuan dari hasil studi ini ditemukan: pertama, Secara keseluruhan, hasil belajar Fiqih siswa yang diberi perlakuan Pembelajaran kooperatif lebih tinggi dari hasil belajar Fiqih siswa yang diberi pembelajaran kompetitif. Kedua, siswa yang memiliki minat belajar tinggi, hasil belajar Fiqih bagi siswa yang diberi perlakuan Pembelajaran kooperatif lebih tinggi dari siswa yang diberi pembelajaran kompetitif. Ketiga, siswa yang memiliki minat belajar rendah, hasil belajar Fiqih bagi siswa yang diberi pembelajaran kompetitif, lebih tinggi dari yang diberi perlakuan Pembelajaran kooperatif. Keempat, Terdapat pengaruh interaksi antara Pembelajaran kooperatif dan kompetitif learning dengan minat belajar (tinggi dan rendah) terhadap hasil belajar Fiqih siswa.